Causal relationship between affect disorders and endometrial cancer: a Mendelian randomisation study - Yewu Sun; Shuo Geng; Chunmeng Fu; Xiaoyan Song; Hua Lin; Yidan Xu (Journal of Obstetrics and Gynaecology)
Background The aim was to assess the causal relationship between depression and anxiety disorders and endometrial cancer.Method We performed two-sample Mendelian randomisation analysis using summary statistics from genome-wide association studies to assess associations of major depressive disorder, anxiety and stress-related disorders with endometrial cancer. The genome-wide association studies(GWASs) data were derived from participants of predominantly European ancestry included in the Genome-wide Association Research Collaboration. Inverse variance-weighted, MR-Egger and weighted median MR analyses were performed, together with a range of sensitivity analyses.Results Mendelian randomisation analysis showed no statistically significant genetic responsibility effect of anxiety and stress-related disorders on any pathological type of endometrial cancer. Only the effect of major depressive disorder under the inverse variance weighting method increasing the risk of endometrial endometrial cancer (effect 0.004 p = 0.047) and the effect of major depressive disorder under the MR-Egger method decreasing endometrial cancer of all pathology types (effect −0.691 p = 0.015) were statistically significant. Other Mendelian randomisation analyses did not show a statistically significant effect.Conclusion Major depressive disorder(MDD), anxiety and stress-related disorders(ASRD) are not genetically responsible for endometrial cancer. We consider that emotional disorders may affect endometrial cancer indirectly by affecting body mass index. This study provides us with new insights to better understand the aetiology of endometrial cancer and inform prevention strategies.